1999
DOI: 10.1046/j.1365-3083.1999.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Phagocyte‐Stimulating and Th1‐Promoting Cytokines by In Vitro Stimulation of Human Peripheral Blood Mononuclear Cells with Streptococcus pneumoniae

Abstract: Polymorphonuclear granulocytes, which provide a major defence against Streptococcus pneumoniae infections, are attracted to and activated by various cytokines. The aim of this study was to analyse the cytokine response of human peripheral blood mononuclear cells to stimulation with S. pneumoniae. Strains belonging to serogroups 4, 6, 14, 19 or 23, were isolated from nasopharynx, middle ear fluid, cerebrospinal fluid or blood. All strains induced a marked proliferative response of the peripheral blood mononucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…There is increasing evidence that cellular immune mechanisms induce resistance to pneumococcal disease and promote pneumococcal clearance (15,20,30,39) through a TH1-type cellular response (3,33). We found that the levels of expression of IL-12 and IFN-␥ were similar in controls and D11-treated mice 6 h after infection.…”
Section: Discussionmentioning
confidence: 60%
“…There is increasing evidence that cellular immune mechanisms induce resistance to pneumococcal disease and promote pneumococcal clearance (15,20,30,39) through a TH1-type cellular response (3,33). We found that the levels of expression of IL-12 and IFN-␥ were similar in controls and D11-treated mice 6 h after infection.…”
Section: Discussionmentioning
confidence: 60%
“…D11 and NAD both reduced PMN IL-8 secretion compared to their respective controls. Different serotypes of live and killed pneumococci have been shown to stimulate IL-8 release from human cells in vitro to varying degrees (1,2,17,25). To our knowledge, it has not been reported previously that type 8 pneumococci can trigger IL-8 release or that IL-8 release can be regulated by type-specific antibodies to pneumococci.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have suggested that the Th1 immune response was critical in overcoming pneumococcal infection (1,21,23), while IL-17A regulates acquired immunity to pneumococcal colonization, and it could enhance pneumococcal killing by human neutrophils. In addition, IL-17A plays an important role in suppressing pneumococcal nasal carriage in mice vaccinated mucosally (26,27).…”
Section: Discussionmentioning
confidence: 99%